2015
DOI: 10.1016/j.ijgo.2014.10.034
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach to in‐service training of maternal health staff in Cambodian hospitals

Abstract: Key clinical skills in low-resource settings can be improved by implementing CME using simulations and supportive follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Harerimana showed that a comparison between a single longer training (11 days) and a shorter training (6 days) showed no difference in nurses’ ability for classification and treatment of childhood illnesses 20. Many studies endorsed the importance of short, repeated education as a strategy leading to greater retention of knowledge and skills 21–24…”
Section: Resultsmentioning
confidence: 99%
“…Harerimana showed that a comparison between a single longer training (11 days) and a shorter training (6 days) showed no difference in nurses’ ability for classification and treatment of childhood illnesses 20. Many studies endorsed the importance of short, repeated education as a strategy leading to greater retention of knowledge and skills 21–24…”
Section: Resultsmentioning
confidence: 99%
“…Woods et al 71 evaluated the secondary effects of training in a controlled trial. The investigators measured the skills of birth attendants who had undergone training as well as those who had not; in addition, they measured skills among birth attendants who had not directly undergone training but worked with those who did.…”
Section: Secondary Effects Of Nr Trainingmentioning
confidence: 99%
“…Gaps in postnatal care have been identified as an important barrier to improving the continuum of care for improving maternal and newborn health [4]. In Cambodia, maternal mortality has decreased markedly [5], but gaps in equity persist and quality of care remains an important priority [4,6,7].…”
Section: Introductionmentioning
confidence: 99%